Will Gorlitz : nowhere if not here - Gorlitz, Will, 1952- (Book collections on Project MUSE., 2009)
Will Gorlitz: nowhere if not here examines the art, background, and theoretical concerns of contemporary Canadian artist Will Gorlitz. Appreciated especially for his painting and drawing, Gorlitz produces imaginative and highly visual artwork that is further distinguished by its fundamentally restructured and critically extended approach to representational painting. With differing emphases from several contributing writers, this book identifies the contexts, methodologies, and motivations that comprise the artist's practice over the past 25 years. The book is published in.